Intranasal infection of beige mice with Mycobacterium avium complex: role of neutrophils and natural killer cells. - Saunders, B M (1996)
Beige mice show increased susceptibility to intranasal infection with organisms of the Mycobacterium avium complex (MAC) compared with their immunocompetent congenics, C57BL/6 mice. This increased susceptibility was clear 2 weeks postinfection, before the activation of the specific immune response. T lymphocytes from 4-week infected beige mice, cultured in vitro, produced amounts of gamma interferon similar to those found in cells from C57BL/6 mice. Macrophage activation, as judged by NO production and lysis of the macrophage target P815, occurred in the lungs of beige mice. Despite the inability of bone marrow-derived NK cells from beige mice to lyse NK-susceptible YAC-1 cells, their gamma interferon production was normal. Monoclonal antibody to NK1.1 was used to deplete C57BL/10 mice of lytic activity against YAC-1 cells without exacerbating infection between 2 and 6 weeks of observation, making it unlikely that any deficiency in NK cells was the cause of susceptibility in beige mice. There was a striking influx of neutrophils in the lungs of beige mice compared with C57BL/6. More than half of the MAC organisms appeared associated with the neutrophils of beige mice, while in C57BL/6 mice, most MAC organisms were associated with cells of macrophage/monocyte morphology. Injection of monoclonal antibody specific for neutrophils failed to eliminate those cells from the lungs of beige mice. However, in C57BL/6 mice, neutrophil numbers were reduced by 95% without exacerbating the infection. We conclude that, although neutrophils are not essential to the relative resistance of C57BL/6 mice, the known deficiencies in both neutrophils and macrophages account for the susceptibility of beige mice.